224k views
1 vote
Solve this equation: -7x + 12 – 2x = 23 + 13x

1 Answer

6 votes

Answer:

x= -1.2

Explanation:

Simplifying

-7 + 12 + -2x = 23 + 13x

Combine like terms: -7 + 12 = 5

5 + -2x = 23 + 13x

Solving

5 + -2x = 23 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.

5 + -2x + -13x = 23 + 13x + -13x

Combine like terms: -2x + -13x = -15x

5 + -15x = 23 + 13x + -13x

Combine like terms: 13x + -13x = 0

5 + -15x = 23 + 0

5 + -15x = 23

Add '-5' to each side of the equation.

5 + -5 + -15x = 23 + -5

Combine like terms: 5 + -5 = 0

0 + -15x = 23 + -5

-15x = 23 + -5

Combine like terms: 23 + -5 = 18

-15x = 18

Divide each side by '-15'.

x = -1.2

User Christofer
by
5.1k points